2006
DOI: 10.1097/01.meg.0000231750.68513.6c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antitumor drugs on the expression of Fas system in SW480 colon cancer cells

Abstract: Certain antitumor drugs can change the expression of the Fas system in SW480 cells in different ways. In vitro, MMC and CP can increase the sensitivity of colon cancer cells to apoptosis signals, but they possibly facilitate immune escape of tumor cells. 5-FU results in immune escape of colon cancer cells. ATRA can down-regulate the possibility of counterattack of colon cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Some Studies have shown that some tumor cells such as colon cancer, gastric cancer, pancreatic cancer express FasL [6,7] . Tumor specific antigen induces tumor infiltrating lymphocytes (TILs) to express high level of Fas, so that T lymphocytes are sensitive to apoptosis [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Some Studies have shown that some tumor cells such as colon cancer, gastric cancer, pancreatic cancer express FasL [6,7] . Tumor specific antigen induces tumor infiltrating lymphocytes (TILs) to express high level of Fas, so that T lymphocytes are sensitive to apoptosis [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some tumor cells such as colon cancer, gastric cancer, pancreatic cancer express FasL [7][8][9][10]. Tumor specific antigen induces tumor infiltrating lymphocytes (TILs) to express high level of Fas, so that T lymphocytes are sensitive to apoptosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al demonstrated that low-dose, metronomic chemotherapy with Cis (0.6 mg/kg/day) dramatically inhibits tumor growth without apparent body weight loss and significant upregulation of Fas (CD95) mRNA and protein in SW480 colon cancer cells and oral cancer cell lines. It is possible for low-dose Cis to attenuate inflammatory responses by inducing Fas expression on effector T cells (2123). We found that although 5-FU at 10 mg/kg demonstrated moderate antitumor effects, no severe side effects were observed.…”
Section: Discussionmentioning
confidence: 99%